Fish Diversity and Histological Characteristics of Female Gonads in the Tripa Peat Swamp Ecosystem, Aceh, Indonesia - Sari, Widya; Anandita, Munreza; Devira, Cut Nanda; Fithri, Aida; Kusuma, Hendrix (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Fish reproductive condition is widely recognized as a sensitive biological indicator of ecosystem health because reproductive processes are strongly influenced by environmental conditions. This study aims to inventory fish species and analyze the reproductive condition of female fish through gonad and histology studies as indicators of the health of the Rawa Tripa ecosystem. Fish samples were collected at 6 location and then were identified to the species level. Reproductive analysis was performed on female fish by observing the level of gonadal maturity and histological preparations to observe the structure of the oocytes. In addition, water quality parameters such as temperature, pH, and dissolved oxygen were measured in situ to support ecological interpretation. The results of the study obtained 88 fish individuals consisting of 12 families and 23 species. The fish species with the most individuals found during the study were Mystacoleucus marginatus, Osteochilus kappenii, Osteochilus hasseltii, Rasbora lateristriga, with 10 individuals each. Only 5 of the 37 examined female individuals (13.5%) exhibited mature gonads, whereas the remaining 32 individuals (86.5%) were in earlier developmental stages. The histology of female fish gonads was obtained from five species, namely Channa lucius, Oreochromis niloticus, Mystacoleucus marginatus, Osteochilus hasseltii, and Osteochilus kappenii. The Tripa Peat Swamp exhibited acidic water conditions (pH 4–7), with temperatures of 25–30°C and dissolved oxygen concentrations of 3–7 mg/L, which may have contributed to the low number of species with mature female gonads, suggesting environmental constraint on reproductive development. Abstrak: Kondisi reproduksi ikan secara luas diakui sebagai indikator biologis yang sensitif terhadap kesehatan ekosistem karena proses reproduksi sangat dipengaruhi oleh kondisi lingkungan. Penelitian ini bertujuan untuk menginventarisasi jenis ikan serta menganalisis kondisi reproduksi ikan betina melalui kajian gonad dan histologi sebagai indikator kesehatan ekosistem Rawa Tripa. Pengambilan sampel ikan dilakukan pada 6 titik perairan rawa, kemudian diidentifikasi hingga tingkat spesies. Analisis reproduksi dilakukan pada ikan betina melalui pengamatan tingkat kematangan gonad dan preparat histologi untuk mengamati struktur oosit. Selain itu, parameter kualitas air seperti suhu, pH, dan oksigen terlarut diukur secara in situ untuk mendukung interpretasi ekologis. Hasil penelitian diperoleh sebanyak 88 individu ikan yang terdiri dari 12 famili dan 23 spesies. Spesies ikan dengan individu paling banyak yang ditemukan saat penelitian adalah Mystacoleucus marginatus, Osteochilus kappenii, Osteochilus hasseltii, Rasbora lateristriga, yaitu masing-masing sebanyak 10 individu. Hanya 5 dari 37 individu betina yang diteliti (13,5%) yang menunjukkan gonad yang sudah matang, sedangkan 32 individu lainnya (86,5%) masih berada pada tahap perkembangan yang lebih awal. Histologis gonad betina ikan yang didapatkan berasal dari 5 spesies yaitu, Channa lucius, Oreochromis niloticus, Mystacoleucus marginatus, Osteochilus hasseltii, dan Osteochilus kappenii. Rawa Gambut Tripa menunjukkan kondisi air yang bersifat asam (pH 4–7), dengan suhu 25–30°C dan konsentrasi oksigen terlarut 3–7 mg/L, yang mungkin menjadi salah satu faktor penyebab rendahnya jumlah spesies dengan gonad betina yang matang, sehingga mengindikasikan adanya kendala lingkungan terhadap perkembangan reproduksi.